Impact of Employees' Workplace Environment on Employees' Performance: A Multi-Mediation Model - Zhenjing, Gu; Chupradit, Supat; Ku, Kuo Yen; Nassani, Abdelmohsen A.; Haffar, Mohamed (Frontiers in Public Health, 2022)
This research examined the impact of workplace environment on employee task performance under the mediating role of employee commitment and achievement striving ability. For this purpose, data was collected from the academic staff under a cross-sectional research design, and they were approached through convenience sampling technique. As per recommendations of established sample size criteria, we distributed a sum of 420 questionnaires among the respondents. Of these distributed questionnaires, only 330 were received back. The returned questionnaires were checked for missing and incomplete responses and after discarding the missing responses useable responses were 314 which were used for the data analysis. Data has been analyzed through structural equation modeling by using Smart PLS 3. Structural equation modeling was done based on measurement models and structural models. Results indicate that a positive work environment has the power to improve employee performance. Similarly, a positive work environment also improves employee commitment level and achievement striving ability significantly. Both employee commitment and achievement striving ability also improve employee performance. While in the case of mediation, it has also been observed that workplace environment triggers employee commitment and employee achievement striving ability which further improves employee performance.